Major causes of continued international payments instability - W. J. Feuerlein (Intereconomics, 1976)
When the Bretton Woods system collapsed in December 1971 the expectation was that a reformed monetary system could be introduced within a year or two. The following article discusses the question why, contrary to this general expectation, the international instability in payments still exists and no end is in sight.
Keywords: 330; Monetary Policy